2022
DOI: 10.1186/s12284-022-00589-x
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Metabolic Profiles and Gene Mapping of Rice (Oryza sativa L.) Purple Gradient Grain Hulls

Abstract: Rice (Oryza sativa L.) grain hull color is an easily observable trait and regarded as a crucial morphological marker in rice breeding. Here, a purple gradient grain hull mutant (pg) was found from natural mutations of a straw-white grain hull rice variety IARI 6184B (Orzya sativa L. subsp. indica). The color of the mutant grain hulls changed from straw-white to pink, then purple, and finally brownish-yellow. Ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) identified 217 flavonoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Similarly, a CSSL population with average donor introgression of 2% was developed [18] and it was observed that substituted segments of donor parent (Yangdao 6) constituted on an average of 5% of the whole rice genome [19]. Three sets of CSSLs with greater coverage of substituted segments were developed [8] using various donor-recipient combinations. In another study, 93.37% of the whole donor genome was covered [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a CSSL population with average donor introgression of 2% was developed [18] and it was observed that substituted segments of donor parent (Yangdao 6) constituted on an average of 5% of the whole rice genome [19]. Three sets of CSSLs with greater coverage of substituted segments were developed [8] using various donor-recipient combinations. In another study, 93.37% of the whole donor genome was covered [20].…”
Section: Discussionmentioning
confidence: 99%
“…The successful application of novel QTL in rice improvement via CSSLs is well documented [5,6,7]. In addition, certain distinct morphological characteristics of wild rice that are derived from CSSLs were utilized as useful phenotypic markers in rice breeding programs [8]. Thus, this investigation aimed to develop two sets of CSSLs in the genetic background of the rice variety K343, followed by their characterization in terms of the genomic contribution of donor lines DHMAS and RML 22.…”
Section: Characterization Of Chromosomal Segment Substitution Lines D...mentioning
confidence: 99%
“…In tetraploid rice, the protein and amino acid levels rise, but the amylose concentration frequently declines ( Wang et al., 2022c ). Functional proteins, oils, vitamins, flavonoids, trace minerals, necessary amino acids, and functional and essential proteins are unique nutritional components found in rice ( Nam et al., 2018 ; Yang et al., 2019 ; Sabooni and Gharaghani, 2022 ; Zhang et al., 2022 ). Strong antioxidant properties of flavonoids were demonstrated by their ability to directly scavenge free radicals, inhibit the production of free radicals by the enzyme oxidase, chelate metal ions produced by free radicals, and promote the regeneration of antioxidant enzymes and small-molecular antioxidant factors ( Bors and Michel, 2002 ; Borges-Bubols et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics is a powerful tool for detecting metabolites within metabolic pathways, revealing distinct differences in flavonoid metabolite synthesis among colored rice varieties 42 .Using the UPLC–MS/MS platform, LvH bran was found to typically have elevated levels of apigenin derivatives, catechin gallate, diosmetin derivatives, epicatechin gallate, and tricin-4′- O -(guaiacylglycerol)ether-7- O -glucoside compared to HeiH, HongH, and GJG. In addition, LvH bran had significantly higher levels of 23 flavonoids that were present at low levels in HeiH bran.…”
Section: Discussionmentioning
confidence: 99%